RELIGIOUS ENVIRONMENT: Penciptaan Suasana Religius di Sekolah - Minhaji Minhaji; Nurul Qomariyah (LP2M Universitas Ibrahimy, 2016)
Religious Education is a field of study that must be given to students at each level of education, where implementation has become a national commitment, so its presence becomes an absolute element in the moral formation of the Indonesian nation. There have been many deviation and moral degradation, as a result of the development of science and technology education.Thereforeneed to be applied in view of Islamic education to the creation of a religious atmosphere in the school environment that is not enough to do in the classroom.The creation of a religious atmosphere in the school is very urgent to implemented. Because that processisthe process of spiritual upliftment and creation of learner’s faith tosubmit to God Almighty andalso noble characters.Noble characters include moral cultivation as the realization of the purpose of Islamic education